MINIMIZING THE DETENT FORCE IN PERMANENT MAGNET LINEAR SYNCHRONOUS MOTOR FOR DRIVING OF 2D LASER MARKING TABLE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this paper the research results for reducing the detent force in one innovative permanent magnet linear synchronous motor for 2D laser marking system was published. There two methods are used. The first of these methods features the usage of two additional end teeth with chamfers in the magnetic circuit of the movable part. In the second method, the teeth of the ferromagnetic core are with different lengths. As a result of the change of the air gap permeance in both cases substantial reduction of detent force is achieved, in multiples at times. The results obtained are based on modeling and analyzing the linear motor magnetic field by the Finite Element Method (FEM). Provided experimental research of the linear motor prototype proves the correctness of the simulations results.